Pengembangan Cleansing Oil Berbasis Minyak Biji Alpukat (Persea americana Mill.) dengan Variasi Konsentrasi Surfaktan sebagai Pembersih Make-Up Tahan Air - Adek Chan; Ervina Syahfitri Lubis; Hendri Faisal; Osy Devitania (Jurnal Indah Sains dan Klinis, 2025)
Background: Avocado seeds contain 15–25% oil and are rich in bioactive compounds such as alkaloids, flavonoids, tannins, saponins, and terpenoids, making them a potential natural ingredient for skincare formulations. Objective: This study aimed to develop a cleansing oil using avocado seed oil with varying surfactant concentrations to evaluate its effectiveness in removing waterproof makeup. Method: The oil was extracted from avocado seeds using the Soxhlet method with n-hexane, yielding 20% oil. Cleansing oil formulations were prepared using surfactant concentrations of 4%, 6%, and 8%, and tested for organoleptic characteristics, homogeneity, pH, irritation, viscosity, stability, user preference, and cleansing performance. Result: All formulations showed safe pH levels (6.4–7.0), no skin irritation, good physical stability, and were well accepted by users. The formulation with 8% surfactant demonstrated the best cleansing ability. Conclusion: Avocado seed oil is suitable for use in cleansing oil formulations, particularly when combined with higher surfactant concentrations, offering an effective and natural solution for removing waterproof makeup